2019
DOI: 10.1007/jhep07(2019)055
|View full text |Cite
|
Sign up to set email alerts
|

Extremal and near-extremal black holes and near-CFT1

Abstract: We study the behaviour of extremal and near-extremal black holes at low energies and low temperatures and find that it can be understood from the near-horizon AdS 2 region. Our analysis includes charged matter and also goes beyond the S-wave approximation. We find that the leading behaviour at low energies arises from a mode linked to time reparametrisations and from phase modes arising from gauge fields. At somewhat higher energies, additional modes arising from higher partial waves can also be cumulatively s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 81 publications
(77 reference statements)
4
97
0
Order By: Relevance
“…Another motivation is to explore the effect of 't Hooft anomalies in random matrix theory. Finally, we expect that aspects of this setup (although not the exact connection to random matrix theory) will be relevant for the bulk description of SYK-like theories with global symmetry [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Another motivation is to explore the effect of 't Hooft anomalies in random matrix theory. Finally, we expect that aspects of this setup (although not the exact connection to random matrix theory) will be relevant for the bulk description of SYK-like theories with global symmetry [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…And so the persistent trend in nAdS 2 holography, coined with a 'n' since we are 'near' to our original configuration, is that the deviations away from extremality are controlled by this pattern. For a review see [14].The application of this new framework to black hole physics has shown that, while JT models capture common features [15][16][17][18][19][20], the additional parameters for more general black holes display interactions that are not present in JT gravity [21][22][23][24][25][26][27]. This makes clear that there is new phenomena to be explored, that simpler models do not take into account.Our interest therefore is to further explore the properties of nAdS 2 /nCFT 1 with the goal of building a more refined understanding of the dynamics near the horizon of (near-)extremal black holes.…”
mentioning
confidence: 99%
“…It is an open question to account for non-extremal black hole entropy from dual field theory. If the qCGHS model can be embedded in higher dimensional black holes, one can hope to gain a better understanding of non-extremal black holes along the line of recent developments [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Among many other interesting papers, partial references include[17][18][19][20][21][22][23]. We apologize for our ignorance about any other important works.…”
mentioning
confidence: 99%